2015
DOI: 10.1016/j.exger.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone, insulin-like growth factor-1 and the aging brain

Abstract: Growth hormone (GH) and insulin-like growth factor (IGF)-1 regulate the development and function of cells throughout the body. Several clinical diseases that result in a decline in physical and mental function are marked by mutations that disrupt GH or IGF-1 signaling. During the lifespan there is a robust decrease in both GH and IGF-1. Because GH/IGF-1 are master regulators of cellular function, impaired GH and IGF-1 signaling in aging/disease states leads to significant alterations in tissue structure and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 87 publications
6
126
0
4
Order By: Relevance
“…Considering that local IGF-1 production within the bone is important for bone development and mineralization (as reviewed by (52) ), it is possible that the loss of circulating IGF-1 only stunted longitudinal growth while local IGF-1 signaling was maintained or even increased, serving as an anabolic signal even in advanced age. This hypothesis would be supported by previous studies showing that the loss of circulating IGF-1 is associated with an increase in the local production of IGF-1 and the IGF-1 receptor in other cell types (53,54) . Within our study, the loss of circulating IGF-1 in female mice did not result in a significant increase in local production of IGF-1, IGF-2, or the IGF-1 receptor.…”
Section: Discussionsupporting
confidence: 63%
“…Considering that local IGF-1 production within the bone is important for bone development and mineralization (as reviewed by (52) ), it is possible that the loss of circulating IGF-1 only stunted longitudinal growth while local IGF-1 signaling was maintained or even increased, serving as an anabolic signal even in advanced age. This hypothesis would be supported by previous studies showing that the loss of circulating IGF-1 is associated with an increase in the local production of IGF-1 and the IGF-1 receptor in other cell types (53,54) . Within our study, the loss of circulating IGF-1 in female mice did not result in a significant increase in local production of IGF-1, IGF-2, or the IGF-1 receptor.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, while central insulin was minimally effective at improving whole‐body insulin action in old animals, central IGF‐1 acted via a dual mechanism, involving suppression of HGP and increased glucose disposal, to markedly improve insulin sensitivity. This observation, coupled with the known protective effects of IGF‐1 on disease risk, particularly in the brain (Ashpole et al ., 2014), highlights a larger emerging paradox regarding the relevance of IGF‐1 to aging in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that low IGF‐1 action may be protective from some diseases, such as cancer, but predispose to others, is particularly relevant to older humans, where somatopause leads to age‐related declines in GH/IGF‐1 (Ashpole et al ., 2014). This prompted many investigators to suspect that the decline of this axis may be causal to many aging phenotypes and that replacement could reverse some manifestations of aging (Rudman et al ., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rodents focused on the IGF-1 axis have been most well studied, and have revealed that IGF-1 levels in circulation, CSF and brain tissue decline with advancing age in some strains, while expression of the IGF-1R in various regions of the CNS either increases, decreases, or remains unchanged (Ashpole et al, 2015; Huffman et al, 2016). Evidence regarding the role of local GH and IGF-1 in cognition is limited, but expression of GH and IGF-1 in the hippocampus of dwarf mice was found to be paradoxically increased, suggesting that maintenance of adequate IGF-1 levels in the brain may be critical to normal cognitive function in these mice (Sun et al, 2005).…”
Section: Gh/igf-1 Axis and Age-related Diseasesmentioning
confidence: 99%